Symbiotic nitrogen fixation for sustainable chickpea yield and prospects for genome editing in changing climatic situations - Mahto, Rohit Kumar; B. S., Chandana; Singh, Rajesh Kumar; Kumar, Arun; Kumar, Sudhir; Yadav, Renu; Dey, Debashish; Hamwieh, Aladdin; Kumar, Rajendra (Frontiers in Plant Science, 2025)
Chickpea (Cicer arietinum L.) is a vital/essential legume crop valued for its nutritional, agricultural, and economic importance, with a relatively large genome size of approximately 738 megabases. Chickpea roots establish symbiotic relationships with soil microorganisms, resulting in the formation of root nodules essential for biological nitrogen fixation. In this study, 20 chickpea genotypes were selected from a genome-wide association panel to assess nodulation traits under eight different treatment combinations involving biofertilizers (Rhizobium, vesicular-arbuscular mycorrhiza - VAM) and inorganic fertilizers (NPK) using a randomized block design with three replications. Pre-planting soil preparation included the application of fertilizers and biofertilizers. Comprehensive analyses including descriptive statistics, correlation, path analysis, principal component analysis, agglomerative hierarchical clustering, and gene expression studies were conducted. Among treatments, the NPK+Rhizobium combination significantly enhanced nodulation across genotypes, while the Rhizobium+VAM (T7) treatment identified ICC-9085 as a superior donor for the number of nodules, aiming for sustainable chickpea productivity. Gene expression profiling through qRT-PCR revealed that the RZ+VAM treatment notably upregulated several key genes, including CaNFP, GST, Leghemoglobin, Nodulin6, and CaLYK3, with CaNFP emerging as a pivotal regulator of nodulation. The marked upregulation of CaNFP underlines its potential as a target for enhancing symbiotic efficiency. The availability of the chickpea draft genome opens new avenues for employing genome editing tools such as CRISPR/Cas systems. Targeted editing of the CaNFP gene offers a promising strategy to improve nodule formation, nitrogen fixation, and overall plant vigor. Integrating CaNFP gene through genome editing with potential genotypes and use of microbial treatments can accelerate the development of elite chickpea cultivars, enhancing productivity while reducing reliance on chemical fertilizers and supporting sustainable agricultural practices.